Plasticity of the forms or cartographies of desire. A reading of Armonía Somers's La mujer Desnuda (El Taco en la Brea, 2020)
In this text we propose a reading of La mujer desnuda of Armonía Somers from a materialism of desire. We do not only postulate a kind of cartography of desire (understood as a revelation of a vacuum, essentially different from the static reality), we also propose on its connection with a form of materiality (from Malabou's plasticity concept) where body, contact and contagion are assumed from a materialism where the form does not coincide with its presence. The materialism that we find in this nouvelle of Somers (an erotic materialism?) allows, on the one hand, to recognize in his character the desire itself (without an object, desire for desire) and, on the other, to map in his movements, the plasticity of the forms that are played as the opening to the form of the other in itself: convertibility of the in-human form and desire to go beyond the notion of community (hinking of those forms and experiences that occur between the loneliness and the community, between the crowd and the singularity).
Keywords: materialism; desire; inhumanity; common; plasticity